A caça e o tráfico de animais silvestres : estratégias para a gestão de políticas públicas na caatinga - Santos, Micaele Karolaine Pereira dos (2017)
The present study analyzed the hunting and wildlife trafficking in the neighbourship of the Ecological Station Raso da Catarina (ESEC Raso da Catarina), in Bahia, in order to contribute to environmental conservation strategies for the region. Among the specific objectives was seek to know five dimensions of hunting activity and wildlife trafficking practiced in the study region (socio-demographic profile of hunters and wildlife traffickers; behavior of hunters and traffickers, hunting profile, economic aspects involved in hunting and, the knowledge of the prohibition of illegal activities against wildlife and mitigation strategies). Also looked for to identify the network of agencies potentially involved in combating the hunting and wildlife trafficking, their strategies and difficulties of action, through the method of research in data and methodological triangulation, based on semi-structured interviews with hunters, employees of the ICMBio of ESEC Raso da Catarina and police officers of the Caatinga Independent Policing Company (Companhia de Policiamento Independente da Caatinga - CIPE / Caatinga); analysis of ICMBio infraction records, police reports records of CIPE / Caatinga and the Federal Highway Police (Polícia Rodoviária Ferderal - PRF). The results indicated that most hunters had between 41 and 50 years old, had incomplete primary education, were in majority farmers and residents of the Riacho Village, municipality of Paulo Afonso, Bahia. As for the most hunted species, there was a predominance for the group of birds, with higher value of use for the species arribaçã (Zenaida auriculata) (VU = 0.31), and for the group of mammals, the armadillo-peba (Euphractus sexcinctus) the species with higher value of use (VU = 0.85). Most hunters preferred to use animals as a means of transport, the dog as a hunting technique, and they preferred to hunt on Saturdays and Sundays, often once or twice a month, during nocturnal and rainy periods, motivated by subsistence reasons. All hunters revealed that they are aware of the prohibition on hunting but are unaware of who is responsible for the prohibition. Regarding surveillance, the ICMBio is the agency that is at the forefront of operations to combat hunting and trafficking of animals in the study area. However, it faces difficulties due to lack of resources and integration with other institutions.